Pengembangan Bahan Ajar Berbasis Literasi Digital Sebagai Suplemen SBdP Kelas I Tema 2 - Rofian Rofian; Muhammad Arief Budiman; Dwi Rosmawati (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
This development research aims to determine the feasibility and steps of developing a digital literacy textbook for first grade teachers as reference and companion for teacher books. This research is research and development (RnD). The data analysis technique used is descriptive qualitative and quantitative data analysis techniques. The results of the development are carried out based on the development steps, namely conducting research and collecting information with preliminary studies in the form  interviews and filling out a needs questionnaire, the information obtained is processed and analyzed, planning, developing an initial draft of the product, conducting validation tests with material and media validators, conducting initial field tests in three elementary schools, and revised the results of the trial, at the initial trial stage there was no revision of the teacher's assessment of the media. Based on the results of the study, the teaching materials developed were included in the "Very Good" and "appropriate" categories for teachers as a reference and companion for teachers' books because the results of material expert validation obtained a percentage of 93.3%, the results of media expert validation obtained a percentage of 98.75% and the average result of the teacher's response questionnaire assessment obtained a percentage of 98%.